2021
DOI: 10.54055/ejtr.v29i.2414
|View full text |Cite
|
Sign up to set email alerts
|

Market segmentation for wine tourism: Identifying sub-groups of winery visitors

Abstract: Notwithstanding the steady development of the international wine tourism industry, accurate relevant information and comparative surveys focusing on primary research appear inadequate in various wine-producing countries. Understanding the wine tourism market is vital for sustaining its further development. In addition to existing typologies for wine tourists, distinctions of winery visitors may provide a valuable tool to help wineries design and implement appropriate marketing tools. Accordingly, the aim of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 58 publications
1
12
0
1
Order By: Relevance
“…Consumer activities in a winery or wine club [48] are crucial for developing and strengthening loyalty to certain brands. Wine tourists plan their visits based on certain information (size of winery, length of stay in the wine region), including various motivating factors [46,[49][50][51][52][53][54]. Educating visitors and other potential consumers is important in building brand loyalty and improving the winery's business performance [55,56].…”
Section: Business Performance Of the Winerymentioning
confidence: 99%
“…Consumer activities in a winery or wine club [48] are crucial for developing and strengthening loyalty to certain brands. Wine tourists plan their visits based on certain information (size of winery, length of stay in the wine region), including various motivating factors [46,[49][50][51][52][53][54]. Educating visitors and other potential consumers is important in building brand loyalty and improving the winery's business performance [55,56].…”
Section: Business Performance Of the Winerymentioning
confidence: 99%
“…In Spain, according to the Association of Spanish Wine Cities (ACEVIN) in its 2019 report [ 93 ], the number of enotourists who visit PDOs is not homogeneous; 3,076,634 people visited wineries and museums along the wine routes of Spain, more than double that of a decade ago. However, despite being a very significant figure, it is still small compared to the 43 million tourist who visited American wineries in 2017, especially considering that Spain is the leading country in the world in terms of vineyard surface area and the third largest wine producer [ 94 ].…”
Section: Enotourism: the Montilla-moriles Routementioning
confidence: 99%
“… Number of visitors and wine routes in Spain (2019). Source: Own elaboration based on ACEVIN data [ 93 ]. …”
Section: Figurementioning
confidence: 99%
“…The study found that post-experience satisfaction increases destination differentiation rather than destination equity. Moreover, Nella and Christou ( 2010 ) measured the impact of tourist experience on brand equity and market outcomes. The study highlights the important role of the tourist experience in terms of the wine industry and its role in enhancing the overall brand equity.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…Malik et al's ( 2021 ) study found that green attributes of destination matter for the tourist, and tourists with favorable attitudes will show an intent to stay loyal due to higher destination brand equity. Similarly, Nella and Christou ( 2010 ) studied the role of real-time experience in product manufacturing and suggested that tasting experience can contribute strongly to destination equity. Stojanovic et al ( 2017 ) found the effective role of social media in developing higher destination equity.…”
Section: Hypothesis Developmentmentioning
confidence: 99%